Calidad del servicio en la atención al cliente del Supermercado Wil Market de la parroquia Febres Cordero, en el periodo 2023. - Yépez Meza, Maylin Noelia (2024)
This case study entitled "Quality of service in customer service at the Wil Market supermarket in the Febres Cordero parish" has the general objective of analyzing the quality of service in customer service provided by the Will Market supermarket to promote customer loyalty and thus also improve the image of the supermarket and increase its sales. Quantitative and qualitative research methods were applied to reinforce the approach to the problems presented, information was collected through research instruments such as the SWOT matrix, structured surveys and semi-structured interviews. In addition, the theoretical bases were reinforced with different sources of expert authors on the subject of customer service quality, since for any company the customer is the most important part so all plans and strategies should be focused and developed based on them and thus Wil Market supermarket reach success.